Strategi Pemasaran Produk Kecantikan Melalui Marketplace Shopee dalam Meningkatkan Penjualan Daviena Skincare Jakarta - Dian Sudiantini; Shanti Komala Dewi; Aditiya Firmansyah; Rizki Hibatullah Kamil; Rizka Maulida Hasan; Ahmad Alief Rahman Faozi (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
The beauty product market in Indonesia has seen significant growth, with marketplaces like Shopee playing a crucial role in sales strategies. This study examines the marketing strategies employed by Daviena Skincare on Shopee to boost sales in, by analyzing various promotional techniques, customer engagement practices, and competitive positioning, this research aims to provide insights into effective online marketing strategies for beauty products. The findings indicate that a combination of targeted promotions, influencer collaborations, and customer feedback integration significantly contributes to increased sales.